Psychology and psychoanalysis (1992)
Based upon thesis by Heidegger and Lacan, the author differentiates psychology from psychoanalysis, taking as a starting point the impropriety of including the latter within the fundamental project of the epoch of science. Such a project is characterized by the decision of constructing scientific knowledge about everything the epoch of science defines under the status of existent. On the contrary, psychology is thought within the project of the epoch, having and object of knowledge substantially different from that of psychoanalysis. If the latter does not have the status of a science, wich status does it have? Along Lacan's line of ideas the autor defines it as an ethical status, fundamental warrant of the psychoanalytical act. Based upon this, new questions arise which are left open .